2015
DOI: 10.5603/imh.2015.0003
|View full text |Cite
|
Sign up to set email alerts
|

Non-cancer diseases requiring admission to hospital among German seafarers

Abstract: (Int Marit Health 2015; 66, 1: 6-10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Considering the 12-month operational time of the crews on board, such high workloads can lead to chronic exhaustion [18,19]. The manifestation of chronic diseases among seafarers is also abundantly described [20,21,22]. Therefore, from the perspective of preventive medicine, a limitation of at least the length of assignment on board seems to be required [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the 12-month operational time of the crews on board, such high workloads can lead to chronic exhaustion [18,19]. The manifestation of chronic diseases among seafarers is also abundantly described [20,21,22]. Therefore, from the perspective of preventive medicine, a limitation of at least the length of assignment on board seems to be required [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of suicide committed at work among seafarers was substantially higher than among the general British population from 1919 to the 1970s [ 3 ]. Many studies have reported hearing and visual impairment; obesity; and diseases of the circulatory, digestive, and musculoskeletal systems among seafarers [ 4 6 ]. Shipping accidents, confined work environments, high consumption of alcohol and tobacco, unhealthy diet, and inadequate physical activity are the major contributing factors to these health problems [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on seafarers’ hospitalizations have used broad categories of respiratory diseases that encompassed all ICD‐10 codes, chronic lung diseases, under the category of respiratory diseases. These results have been somewhat conflicting: seafaring has been associated both with lower 20 and higher 20–22 risk for respiratory diseases, or this association has been marginal 20–22 . Furthermore, a study without formal statistical analysis concluded that infections were more severe in terms of mortality and hospitalizations than noninfectious events among seafarers 14 …”
Section: Discussionmentioning
confidence: 99%